Ethylene and the regulation of plant development - Schaller G (BMC Biology, 2012)
Abstract Often considered an 'aging' hormone due to its role in accelerating such developmental processes as ripening, senescence, and abscission, the plant hormone ethylene also regulates many aspects of growth and development throughout the life cycle of the plant. Multiple mechanisms have been identified by which transcriptional output from the ethylene signaling pathway can be tailored to meet the needs of particular developmental pathways. Of special interest is the report by Lumba et al. in BMC Biology on how vegetative transitions are regulated through the effect of the transcription factor FUSCA3 on ethylene-controlled gene expression, providing an elegant example of how hormonal control can be integrated into a developmental pathway. See research article http://www.biomedcentral.com/1741-7007/10/8 Commentary One of the amazing qualities of plants is their phenotypic plasticity. Consider, for example, how a pine tree will grow to a towering hundreds of feet in height in Yosemite Valley, but to only a gnarled few feet in height up near the timberline. This diversity of form, though originating from the same genotype, points to the degree to which plant growth and development can be modulated. Much of this control is mediated by a small group of plant hormones that include auxin, cytokinin, gibberellin, abscisic acid, brassinosteroid, jasmonic acid, and ethylene <abbrgrp>1</abbrgrp>. These are often considered 'classical' plant hormones because they were discovered decades ago; indeed, the presence of some was inferred over a century ago. Their early discovery is no doubt due in part to their general function throughout the life cycle of the plant. More recently, and in the remarkably short period of time since the advent of Arabidopsis as a genetic model, key elements in the primary signaling pathways of these plant hormones have been uncovered. The important question is no longer simply how are these hormones perceived, but how are the hormonal signals integrated into the control of particular developmental pathways? In pursuing such a question, Lumba et al. <abbrgrp>2</abbrgrp> have now uncovered a role for the plant hormone ethylene in regulating the conversion of juvenile to adult leaves. These new data, in combination with prior research implicating the plant hormones abscisic acid and gibberellin in this transition <abbrgrp>3</abbrgrp>, form an important step in defining how a hormonal network regulates a key developmental process.